2017
DOI: 10.1002/glia.23140
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ACSA-2 defines a novel monoclonal antibody for prospective isolation of living neonatal and adult astrocytes

Abstract: Astrocytes are the most abundant cell type of the central nervous system and cover a broad range of functionalities. We report here the generation of a novel monoclonal antibody, anti-astrocyte cell surface antigen-2 (Anti-ACSA-2). Flow cytometry, immunohistochemistry and immunocytochemistry revealed that Anti-ACSA-2 reacted specifically with a not yet identified glycosylated surface molecule of murine astrocytes at all developmental stages. It did not show any labeling of non-astroglial cells such as neurons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 59 publications
3
65
0
Order By: Relevance
“…As an initial validation of the model, Aldh1l1-NuTRAP mice were systemically delivered Tam for 5 consecutive days and a week after induction, brains were dissected for flow cytometry (FC) and immunohistochemistry (IHC) analyses. Single-cell suspensions of brains immunostained with ACSA-2 antibody, a pan-astrocytic marker 15 , revealed a distinct EGFP + cell population present in the Aldh1l1-NuTRAP brains but not in the cre negative counterparts, consistent with the reported 10-20% astroglial cellularity in the rodent brain 16, 17 , Almost the entirety of the EGFP + cell population co-expressed ACSA-2, supporting that cre-mediated recombination upon Tam induction specifically targeted astrocytes (Figure 1A-B) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an initial validation of the model, Aldh1l1-NuTRAP mice were systemically delivered Tam for 5 consecutive days and a week after induction, brains were dissected for flow cytometry (FC) and immunohistochemistry (IHC) analyses. Single-cell suspensions of brains immunostained with ACSA-2 antibody, a pan-astrocytic marker 15 , revealed a distinct EGFP + cell population present in the Aldh1l1-NuTRAP brains but not in the cre negative counterparts, consistent with the reported 10-20% astroglial cellularity in the rodent brain 16, 17 , Almost the entirety of the EGFP + cell population co-expressed ACSA-2, supporting that cre-mediated recombination upon Tam induction specifically targeted astrocytes (Figure 1A-B) .…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent gating based on CD11b or ACSA-2 expression was done with 640 nm laser and 676/629 filter, or with 488 nm laser and 740 LP filter combinations, respectively. The antibodies used were anti-mouse CD11b: APC (#17-0112, clone M1/70) (eBioscience, San Diego, CA), and ACSA-2: PE-Vio770 (#130-116-246, Milteny Biotec) 15 . Isotype controls for each antibody and unstained cells were used for proper post-color compensation (Supplemental Figures 14-15) .…”
Section: Methodsmentioning
confidence: 99%
“…These include the well-established antibodies against CD45 (36) and O4 (37,38), the astrocyte-specific anti-ACSA-2 antibody that has been recently validated by ourselves and independent groups (27,39,40), (Supplemental Figure 2), and the anti-CD49a antibody ( Figure 1B, Figure 2, and Supplemental Figure 2). Employing the commonly used ALDH1l1-EGFP reporter (41) believed to mark the majority of astrocytes, we found that the anti-ACSA-2 antibody labeled all GFP + astrocytes in addition to a sizable GFP -astrocyte population (Supplemental Figure 3A), suggesting that this reporter line does not mark all astrocytes in adult brains.…”
Section: Concurrent Brain Cell Type Acquisition From a Single Adult Mmentioning
confidence: 99%
“…S1B-C). Astrocytes and Müller cells were isolated using ASCA2+ selection, as reported previously (Kantzer et al, 2017). By 14 days post-injection, ACSA2+ cells exhibited increased levels of pan reactive and A1 astrocyte specific markers ( Fig.…”
Section: Elevated Intraocular Pressure Induces A1 Astrocyte Reactivitmentioning
confidence: 76%